Analysis of temperature behavior in biological tissue in photothermal therapy according to laser irradiation angle - Kim, Donghyuk; Kim, Hyunjung (Bioengineered, 2023)
The type of death of biological tissue varies with temperature and is broadly classified as apoptosis and necrosis. A new treatment called photothermal therapy is being studied on this basis. Photothermal therapy is a treatment technique based on photothermal effects and has the advantage of not requiring incisions and, therefore, no bleeding. In this study, a numerical analysis of photothermal therapy for squamous cell carcinoma was performed. Photothermal agents used were gold nanoparticles, and the photothermal therapy effect was confirmed by changing the angle of the laser irradiating the tumor tissue. The effectiveness of photothermal therapy was quantitatively assessed on the basis of three apoptotic variables. Further, the volume fraction of gold nanoparticles in the tumor tissue and laser intensity with optimal therapeutic effect for different laser irradiation angles were studied. Thus, the findings of this study can aid the practical implementation of photothermal therapy in the future.
Keywords: Carcinoma, Squamous Cell; Gold; Humans; Metal Nanoparticles; Photothermal Therapy; Temperature; Apoptosis; gold nanoparticles; irradiation angle; photothermal therapy; squamous cell carcinoma; thermal damage